NARRATIVE INQUIRY; PERSPECTIVE OF LECTURERS AND STUDENTS IN IMPLEMENTING HYBRID LEARNING PROCESS IN THE NEW NORMAL ERA - Nabila Syafi'atulkhoir (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
This research aims to investigate the implementation of hybrid learning in the perspective of lecturers and students. This research examines the experiences of English lecturers and students in implementing hybrid learning during the new normal era. To capture the teacher's story, an inquiry narrative was adopted. The research data collected based on interview guidelines and presented through narrative frames and narrative boxes. The results indicate that lecturers teach English in hybrid learning by applying different online platforms. Then the campus was focused on using virtual classrooms and WhatsApp as the main platforms in online classes because they had been linked to the campus. In addition, the learning process, internet connectivity, awareness of students' self-study, and learning scheduling are obstacles in applying hybrid learning in the new normal.